Lithuanian Foreign Trade Turnover Forecasting - Morkeliūnas, Algis; Žiaunys, Henrikas (Ekonomika, 2000)
In many countries the index “trade conditions” is ysed to evaluate the effectiveness of foreign trade. It is the ratio of the average price of goods exported and imported by. county, laking into account the specific weight of goods in the total volume of export and import. In case this index is higher than 1, it is considered that the trading conditions and the economic situation of the country has imported: the country can get more imported goods for its export unit.Foreign trade dynamics is not fully expressed by the methods of economic statistics, therefore econometric functions of export and import are calculated, yielding the dynamics of foreind trade based on different indices that describe material production of the country, and the economy of the world. The collections of factors of import and export functions, definite import and export functions for the main foreign trade partners and their parameters of economic reliability are presented in the article.